Analyzing the Different Effects of Endogenous and Exogenous Money Supply on Inflation: A Spectral Analysis Approach - alireza kamalian; Zahra Zamani; mohammad Amirali; mostafa mobini dehkordi (پژوهشهای اقتصادی, 2020)
In recent decades, the inflation phenomenon has been one of the most important issues for Iranian economy. Regardless of its effects on economy, identifying the determinants of inflation has always been a challenge in all economies. Therefore, in order to compare the endogenous money theory with the quantity theory of money, this study analyzes the relationship between inflation and its determinants. To this end, the spectral analysis approach at high and low frequencies is applied during the period 1991: Q1 to 2018: Q1. The results show that there is the causality relationship from the growth of liquidity towards inflation as well as from inflation to liquidity in the short- term and long-term. In addition, there is the causality relationship from the monetary base growth to inflation in the long-term, while this causal relationship runs from monetary base growth towards inflation in the short-term. Moreover, the causality relationship from money multiplier growth to inflation is confirmed in the long-term. Consequently, the causes of inflation are different in the short- and long-term.